Struktur dan Status Regenerasi Alami di Hutan Konservasi Cagar Alam Maninjau Malabur Kabupaten Agam - Nurul Fadhila Ilahi; Irma Leilani Eka Putri (Jurnal Serambi Biologi, 2023)
Data is needed regarding the structure and status of natural regeneration in the Maninjau Nature Reserve Conservation Forest which will be carried out from December 2022 - January 2023. The tools and materials used are labels, raffia rope, plastic bags, stationery, hygrometer, thermometer, lux meter, stake , meter, camera and GPS, carried out in 2 different places, namely natural areas and open/damaged areas. The sample plots used were nested square plots measuring 20x20m, ie 2x2m for the seedling phase, 5x5m for the sapling phase, 10x10m for the pole phase, and 20x20m for the tree phase. In each area 3 plots were placed randomly. Data is processed to obtain vegetation data and analysis of regeneration status. Plants found in natural areas at the seedling level are 12 species, 8 species for saplings, 4 species for poles and 11 species for trees, in open areas for seedlings 10 species, 5 species for saplings, 3 species for poles and 5 species for trees. Overall regeneration status can be said to be good because 7 species (35%) regenerate well, 2 species (10%) have sufficient regeneration, 6 species (30%) have low regeneration and 5 species (25%). In open/damaged areas it has a low regeneration density.